2014
DOI: 10.1186/1476-7120-12-16
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial doppler ultrasonography should it be the first choice for persistent foramen ovale screening?

Abstract: BackgroundPersistent foramen ovale (PFO) is considered a cause of cryptogenic stroke and a risk factor for neurological events in young patients. The reference standard for identifying a PFO is contrast-enhanced transesophageal echocardiography (TEE).The goal of this study was to evaluate the feasibility of transcranial color Doppler (TCD) and its diagnostic sensitivity compared with TEE.MethodsWe investigated 420 patients admitted to our department with cryptogenic stroke, transient ischemic attacks or other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
51
1
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 33 publications
3
51
1
2
Order By: Relevance
“…As previously documented [20,28] we demonstrate moderate agreement between c-TCD and TEE for identifying and grading RLSh. While prior work has suggested that TCD may be a sensitive tool compared to TEE [17,2933], these prior studies were not performed on large numbers of patients with CS and there is no prior work showing that TCD might be better at distinguishing pathogenically important from less important PFOs.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…As previously documented [20,28] we demonstrate moderate agreement between c-TCD and TEE for identifying and grading RLSh. While prior work has suggested that TCD may be a sensitive tool compared to TEE [17,2933], these prior studies were not performed on large numbers of patients with CS and there is no prior work showing that TCD might be better at distinguishing pathogenically important from less important PFOs.…”
Section: Discussionsupporting
confidence: 85%
“…[18,19] Although the ability and relevance of RLSh grade evaluated by c-TCD is unknown, some authors have recommended that c-TCD be the first line screening test to detect RLSh for patients with CS. [20] Herein, we investigate whether shunt grade determined by c-TCD is correlated with RoPE score, and also whether c-TCD and TEE agree with respect to shunt identification and grading.…”
Section: Introductionmentioning
confidence: 99%
“…Because elderly patients are difficult for TCD, there seemed to be selection bias of patients in this study. However, as a method which could quantify right‐to‐left shunt (RLS) directly, c‐TCD has a class IIa recommendation for RLS detection as well as TEE,41 and have been recommended as the first choice for screening PFO 22. When compared with TEE,42 it has been demonstrated that contrast‐TCD is more feasible in elderly patients.…”
Section: Discussionmentioning
confidence: 99%
“…As described previously,8, 22 contrast agent was generated by agitating a mixture of 9 mL of isotonic saline solution and 1 mL of air between two 10 mL syringes connected by a three‐way stopcock. A drop of the patient's blood was allowed to mix with the contrast agent, which can slightly increase the detection sensitivity.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation